PROXIMAL BRACHIAL MONOMELIC AMYOTROPHY OR HIRAYAMA DISEASE: NO LONGER AN ALIAS? (case report) - Akshay Rao (International Journal of Medicine and Medical Research, 2019)
Background. Brachial Monomelic Amyotrophy (BMMA) has been called as Hirayama disease (HD) when it is characterized by unilateral distal upper limb weakness and atrophy that shows progression for a limited period and is associated with typical features on MRI of cervical spine in flexion.